2011
DOI: 10.2147/ccid.s20543
|View full text |Cite
|
Sign up to set email alerts
|

Flutamide versus a cyproterone acetate-ethinyl estradiol combination in moderate acne: a pilot randomized clinical trial

Abstract: BackgroundThe use of oral flutamide is rarely investigated in acne therapy. The aim of this study was to compare the efficacy of oral flutamide with that of a cyproterone-estradiol combination in treating acne lesions.MethodsA randomized clinical trial enrolled patients with moderate acne into two equal groups to receive either oral flutamide or the cyproterone-estradiol combination for 6 months. Lesion count, Acne Severity Index, and Global Acne Grading system (GAGS) scores were used to assess improvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
(13 reference statements)
1
13
0
6
Order By: Relevance
“…Acne appears in skin areas rich in pilosebaceous units, i.e., face, back, and trunk (3). It is attributed to many factors including androgen activity, increase in sebum production, follicular hyperkeratinization, change in sebum lipid quality, and proliferation of Propionibacterium acnes within the follicles (4).…”
Section: Introductionmentioning
confidence: 99%
“…Acne appears in skin areas rich in pilosebaceous units, i.e., face, back, and trunk (3). It is attributed to many factors including androgen activity, increase in sebum production, follicular hyperkeratinization, change in sebum lipid quality, and proliferation of Propionibacterium acnes within the follicles (4).…”
Section: Introductionmentioning
confidence: 99%
“…Its effectiveness in the treatment of acne, hirsutism and androgenetic alopecia has been demonstrated . Of nine studies identified for this review, only one specifically studied the effect of flutamide on acne; the primary focus of the other studies was on hirsutism but all studies found at least a marked improvement in acne compared with baseline and/or placebo and/or comparator products …”
Section: Hormonal Therapy In Acnementioning
confidence: 99%
“…The standard dose used in acne ranges between 62·5 and 500 mg daily, which can result in an 80% improvement of acne. Flutamide can be used alone or in combination with metformin and COCs in patients with PCOS . Hepatic toxicity is the major limitation of this drug and it seems to be dose‐ and age‐related; it is advised to use a low initial dose and subsequently increase it.…”
Section: Hormonal Therapy In Acnementioning
confidence: 99%
“…Spironolactone, which has dual function through androgen receptor blockade and inhibition of 5a-reductase, can reduce sebum production and improve acne [73,74]. Flutamide (FDA-approved for the treatment of prostate cancer) is a non-steroidal androgen receptor blocker that has also been effective, but cost and hepatotoxicity significantly limit its use [75]. Outside of the USA, clinicians can prescribe anti-androgen cyproterone acetate at low dosage (2 mg/day) or higher dosage (50 mg/day) combined with estrogen; of note, patients on higher-dosage cyproterone acetate should be monitored for hepatotoxicity.…”
Section: Oral Hormonal Treatmentmentioning
confidence: 99%